Rutba vs Ġāya: A Reconsideration of the Impact of the Rasāʾil Iḫwān al-Ṣafāʾ on Maslama b. Qāsim al-Qurṭubī - Callataÿ, Godefroid de (Arabica, 2021)
This study aims to reconsider the impact of the Rasāʾil Iḫwān al-Ṣafāʾ on the Rutbat al-ḥakīm (The Rank of the Sage) and the Ġāyat al-ḥakīm (The Aim of the Sage). Exclusively concerned with textual evidence taken from the three works and making extensive use of the programme Qawl, it shows that the way Maslama b. Qāsim al-Qurṭubī refers to the Iḫwānian corpus in the Rutba reveals a far less familiarity with that work than at the time he writes the Ġāya. This difference of treatment suggests that, contrary to what was previously assumed, Maslama had no access to the text of the Rasāʾil before he started writing his ultimate treatise.